2022
DOI: 10.1139/cjz-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

An observational analysis of Canada Jay (Perisoreus canadensis) foraging and caching ecology in Denali National Park and Preserve, Alaska, USA

Abstract: Arctic and subarctic wildlife are among the most vulnerable species to climate change. Canada Jays (Perisoreus canadensis (Linnaeus, 1776)) are generalist residents of northern boreal forests and scatter-hoard food to insulate against food scarcity during winter. Unlike most scatter-hoarders, however, Canada Jays primarily cache perishable food, rendering their caches more susceptible to climate change induced degradation and loss. Here we use a mostly noninvasive approach to document Canada Jay foraging ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Similarly, our compilation of direct observations almost certainly exaggerates the importance of vertebrate flesh in the diet (and minimizes that of arthropods) because observers are more likely to report consumption of familiar vertebrate taxa than of tiny, quickly ingested invertebrates. In contrast, the much lower proportion of vertebrates (24%) reported in a direct-observation study in Denali, Alaska [ 36 ] is probably more accurate because it is based on a much larger sample and because the observers made concerted efforts to record all food acquisitions by focal individuals. However, we also note that differences in diet composition between the APP and Denali population could simply be due to differences in prey composition or climate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, our compilation of direct observations almost certainly exaggerates the importance of vertebrate flesh in the diet (and minimizes that of arthropods) because observers are more likely to report consumption of familiar vertebrate taxa than of tiny, quickly ingested invertebrates. In contrast, the much lower proportion of vertebrates (24%) reported in a direct-observation study in Denali, Alaska [ 36 ] is probably more accurate because it is based on a much larger sample and because the observers made concerted efforts to record all food acquisitions by focal individuals. However, we also note that differences in diet composition between the APP and Denali population could simply be due to differences in prey composition or climate.…”
Section: Discussionmentioning
confidence: 99%
“…We attribute the much greater proportion of apparently fresh items in the nestling diet to the fact that Canada jay nestling period in our study area typically straddles the disappearance of snow cover in mid- to late-April and, in our case, half of our nestling stomachs and fecal sacs were collected considerably later than that, even as late as May 19 (from a replacement nest). Derbyshire et al [ 20 ] previously pointed out that once snow cover has disappeared, Canada jay parents forage for their nestlings on the forest floor where food storage has never been observed and Swift et al [ 36 ] similarly reported that Canada jays in Denali, Alaska “responded to a record-setting warm spring by directing their foraging efforts away from cache recovery and towards the emergence of fresh food”. Together these results lend further support to the suggestion by Strickland and Ouellet [ 22 ] that food storage is the key behaviour in Canada jays permitting not only their high winter survival and territorial fidelity, but also their high nesting success (thanks to the use of stored food as critical “emergency food” in late springs or during the not unusual snow and ice storms that occur in the late-winter Canada jay nesting season).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the causes of variation in incubation behaviour in a species that nests in below-freezing temperatures, we collected incubation data from a population of Canada Jays (Perisoreus canadensis) in Denali National Park and Preserve (hereafter, 'Denali NPP'), Alaska, USA. Canada Jays are year-round residents of North American boreal and subalpine forests that cache a wide variety of perishable food items, such as vertebrate flesh, invertebrates, berries, and fungi, during late summer and autumn, which they subsequently rely on for survival over winter and into the breeding season (March to May) when fresh food may not be readily available (Swift et al 2022). Canada Jays form socially and genetically monogamous year-round pair bonds (Strickland & Ouellet 2020;Fuirst et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Canada Jays are well-known for being territorial throughout the year and consuming a wide variety of foods captured through use of various foraging behaviors. Food is scatter-hoarded in small caches throughout the territory during autumn and winter for use in periods of food shortages (Rutter 1969; Strickland and Ouellet 2020; Swift and others 2022). Prior reports in the literature of Canada Jays feeding on Winter Ticks include those of Hardy (1869) from Nova Scotia, who noted that the jays often picked up ticks (presumably Winter Ticks) from Moose beds on the snow during winter and early spring, and the more detailed observations of Addison and others (1989) from Ontario, which include: (1) a territorial pair and possibly an offspring from the previous year collecting engorged ticks in early April from the beds of a captive infested Moose; (2) a pair of jays landing on a Moose in mid-April and pecking at body regions where ticks concentrate (although no ticks were seen eaten); (3) a pair of jays presented with bread and 11 engorged ticks placed on a white sheet in early May (ticks were rapidly removed, carried up to 3 at a time in the throat while flying, and cached in the nearby forest); and (4) an active nest of jays in late April which contained 3 small nestlings and 3 engorged ticks, one of the ticks still alive.…”
mentioning
confidence: 99%